Exploitation of the fibrinolytic system by B-cell acute lymphoblastic leukemia and its therapeutic targeting - Minciacchi, Valentina R.; Bravo, Jimena; Karantanou, Christina; Pereira, Raquel; Zanetti, Costanza; Kumar, Rahul; Thomasberger, Nathalie; Llavona Juez, Pablo; Krack, Theresa; Bankov, Katrin; Meister, Melanie; Hartmann, Sylvia; et al. (Nature Communications, 2024)
The fibrinolytic system promotes the progression of solid tumors. Here, the authors show that the fibrinolytic agent plasmin supports B-cell acute lymphoblastic leukemia (B-ALL) progression via remodeling of the extracellular matrix, and the inhibition of plasmin activation with ε-aminocaproic acid prolongs survival in B-ALL mouse models.
Gesehen am 22.04.2025